Initial study on electro-mechanical artificial insemination (AI) device for small ruminants - Sahlan, Shafishuhaza; Shikh Maidin, Mashitah (World Scientific and Engineering Academy and Society (WSEAS), 2013)
This paper presents an initial prototype construction of an electro-mechanical artificial insemination (AI) device for goats. AI technique is low cost and simple to perform, however the labor cost is steep for experts. To reduce the cost and increase the accuracy of AI, a device which is capable on visualizing the os of cervix is constructed, along with a built-in circuit utilizing a PIC as its brain. The device functions well as preprogrammed in the PIC, however the operation time is quite slow hence further improvements are required.